Fate of active pharmaceutical ingredients in a northern high-rate algal pond fed with municipal wastewater. (May 2021) - Lindberg, Richard H.; Namazkar, Shahla; Lage, Sandra; Östman, Marcus; Gojkovic, Zivan; Funk, Christiane; Gentili, Francesco G.; Tysklind, Mats
Abstract: Active pharmaceutical ingredients (APIs) are vital to human health and welfare, but following therapeutic use, they may pose a potential ecological risk if discharged into the environment. Today's conventional municipal wastewater treatment plants are not designed to remove APIs specifically, and various techniques, preferably cost-effective and environmentally friendly, are being developed and evaluated. Microalgae-based treatment of wastewater is a sustainable and low-cost approach to remove nutrients and emerging contaminants. In this study, a North Sweden high-rate algal pond (HRAP) using municipal untreated wastewater as medium, was investigated in terms of API distribution and fate. Three six-day batches were prepared during 18 days and a total of 36 APIs were quantified within the HRAP of which 14 were removed from the aqueous phase above 50% and seven removed above 90% of their initial concentrations. Twelve APIs of a hydrophobic nature were mostly associated with the algal biomass that was harvested at the end of each batch. HRAPs treatment successfully removed 69% of studied APIs (25 of 36 studied) in six day time. The distribution of various APIs between the aqueous phase and biomass suggested that several removal mechanisms may occur, such as hydrophobicity driven removal, passive biosorption and active bioaccumulation. Graphical abstract: Image 1 Highlights: Nordic microalgal strains removed pharmaceuticals from wastewater. Removal mechanism likely a combination of biotic and abiotic factors. Several pharmaceuticals were detected in algal biomass. High-rate algal pond treatment is a promising green energy alternative.